The Effect of PjBL with Oral Corrective Feedback on Student Scientific Article Writing Skills - Vivi Indriyani; Ayu Gustia Ningsih; Mita Domi Fella Henanggil; Wilda Fathia (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
The purpose of this study was to determine the effectiveness of using the Project Based Learning model integrated with Oral Corrective Feedback in teaching academic writing in tertiary institutions. This form of research uses an experimental methodology and is quantitative in nature. Matching Pretest-Post-Test Control Group Design was used as the research methodology. This research data collection strategy uses tests. The test given is a performance test, in which students make scientific articles to be published in journals. The research data processing technique was SPSS 17. Based on the findings and discussion it can be concluded that the use of the PjBL model integrated with Oral Corrective Feedback is more effective than using the PjBL model alone to teach students academic writing in the field. Indonesian Language and Literature Study Program, Padang State University. The use of this model is one of the innovations in learning based on the latest curriculum by integrating innovative language learning methods in learning in tertiary institutions.